Periodic trends in constants of triatomic molecules. Issue 14 (29th March 2016) - Barrow, Joshua; Caviness, Ken; Hefferlin, Ray; Nash, Devin
Abstract : Working from the arrangements of both row and group numbers developed within Mendeleev's periodic table of elements, periodic trends can be shown to exist in many constants of triatomic molecules: an extension of the Periodic Law for atoms to the realm of molecules. Trends are identified for vibrational frequencies, bond lengths, and to a lesser extent interior angles. This work includes empirical sources for such data, supplemented with calculations using diatomic analogs where possible. Otherwise, computation is used for all possible configurations of row two and row three main‐group elements to both corroborate and extend empirical results. Organization of this data into a detailed, highly symmetric, multidimensional coordinate system allows for robust graphical and statistical analysis of all constants and associated trends, which in turn permits rapid identification of suspect data to be rechecked. All collected empirical and computational data, along with several interactive visualizations highlighting these results, is available online. © 2016 Wiley Periodicals, Inc. Abstract : This work shows there exists periodic behavior across all triatomic molecules in consideration of their vibrational frequencies, and to a lesser extent their bond lengths and angles, as compiled from both experimental studies and computational simulations. A Mendeleevian numbering scheme of group/row number coordinates to make a highly‐symmetric, 13‐dimensional form is used. These results restate the Periodic Law in a molecular rather than elemental sense, a satisfying but not necessarily expected result, given quantum mechanical complexity.